2020
DOI: 10.3389/fphys.2020.573700
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Resonance Reduces Sway and Gait Variability in Individuals With Unilateral Transtibial Amputation: A Pilot Study

Abstract: Sub-threshold (imperceptible) vibration, applied to parts of the body, impacts how people move and perceive our world. Could this idea help someone who has lost part of their limb? Sub-threshold vibration was applied to the thigh of the affected limb of 20 people with unilateral transtibial amputation. Vibration conditions tested included two noise structures: pink and white. Center of pressure (COP) excursion (range and root-meansquare displacements) during quiet standing, and speed and spatial stride measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 98 publications
0
16
1
Order By: Relevance
“…Specifically, Likens et al applied subthreshold vibration to the residual limb thigh among adults post-TTA (n=20), reducing postural sway and gait variability. 41 Although currently experimental, the use of vibratory technologies may provide augmented somatosensory feedback to overcome loss of the anatomic foot, and the environment inherent to the prosthesis-limb interface, to enhance functional balance post-TTA, particularly because vibratory thresholds appear to be preserved postamputation, in the absence of dysvascularity and pain.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Likens et al applied subthreshold vibration to the residual limb thigh among adults post-TTA (n=20), reducing postural sway and gait variability. 41 Although currently experimental, the use of vibratory technologies may provide augmented somatosensory feedback to overcome loss of the anatomic foot, and the environment inherent to the prosthesis-limb interface, to enhance functional balance post-TTA, particularly because vibratory thresholds appear to be preserved postamputation, in the absence of dysvascularity and pain.…”
Section: Discussionmentioning
confidence: 99%
“…Impaired balance may lead to individuals avoiding certain activities, compounding some morbidities (Patla and Shumway-Cook, 1999). However, improving the somatosensation of the residual limb may improve standing balance (Quai et al, 2005;Likens et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been suggested that the vestibular system uses SR to amplify sound to ward off hearing loss, presenting as tinnitus, or conductive hearing loss (Krauss et al, 2016). In the context of human movement, applying subthreshold vibration at or proximal to the site of interest has been associated with improvements in balance, proprioception, gait, and sensation (Gravelle et al, 2002;Liu et al, 2002;Khaodhiar et al, 2003;Priplata et al, 2006;Stephen et al, 2012;Enders et al, 2013;Kundu and Sarkar, 2015;Lakshminarayanan et al, 2015;Lipsitz et al, 2015;van der Groen and Wenderoth, 2016;Hathibelagal, 2018;Temple et al, 2018;Seo et al, 2019;Zandiyeh et al, 2019;Likens et al, 2020;Zwaferink et al, 2020). Notable areas of improvement in individuals with amputation include SR reducing COP sway, gait variability, and single leg stances measures (Lee et al, 2007;Likens et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations